Nursing work in the COVID-19 pandemic and repercussions for workers' mental health - Norma Valéria Dantas de Oliveira Souza; Eloá Carneiro Carvalho; Samira Silva Santos Soares; Thereza Christina Mó Y Mó Loureiro Varella; Sandra Regina Maciqueira Pereira; Karla Biancha Silva de Andrade (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To reflect about the work context of nursing professionals in the COVID-19 pandemic and the repercussions for these professionals' mental health. Method: This is a theoretical reflective study with two thematic axes: i) Pandemic by COVID-19: epidemiological condition, manifestations, and preventive measures; ii) Precariousness of work in times of pandemic and impacts on the worker's mental health. Results: The COVID-19 pandemic made explicit the reflects of precariousness in the health sector. For example, the psychological suffering of nursing workers was evidenced due to the scarcity of personal protective equipment, the weakness in the description of the protocols and the flows for the effective control of infections, the long working hours, the inadequate professional training for crisis scenario and uncertainty in relation to therapeutic measures. Conclusion: The present article brings to light the aggravation of a scenario that raises the potential for negative impact on the mental health of nursing workers.